[68Ga]Ga-PSMA-11 PET/CT in medullary thyroid carcinoma: comparison with [18F]FDG PET/CT and immunohistochemical analysis - Zajkowska, Klaudia; Bakuła-Zalewska, Elwira; Cegla, Paulina; Wojewódzka-Mirocha, Marta; Ochman, Paweł; Sackiewicz, Agata; Januszkiewicz-Caulier, Joanna; Długosińska, Joanna; Czetwertyńska, Małgorzata; Dedecjus, Marek (Frontiers in Endocrinology, 2025)
IntroductionMedullary thyroid carcinoma (MTC) is a rare neuroendocrine malignancy. Despite the use of various imaging modalities, including positron emission tomography combined with computed tomography (PET/CT), a significant proportion of patients with biochemical evidence of disease have no detectable lesions. Prostate-specific membrane antigen (PSMA) is expressed by the neovasculature of several solid tumours, including thyroid cancer. While case reports suggest that PSMA-targeted PET/CT may detect MTC lesions, its diagnostic value remains unverified. This study aimed to compare the clinical utility of [68Ga]Ga-PSMA-11 PET/CT with that of 2-[18F]fluoro-2-deoxy-D-glucose ([18F]FDG) PET/CT in MTC patients, assess PSMA expression by immunohistochemistry, and correlate PSMA expression with [68Ga]Ga-PSMA-11 PET/CT findings.MethodsTwelve patients with MTC who had undergone total thyroidectomy and presented with elevated serum calcitonin and/or carcinoembryonic antigen levels underwent prospective evaluation with [68Ga]Ga-PSMA-11 and [18F]FDG PET/CT. Immunohistochemical staining for PSMA and CD31 was performed.ResultsThe detection rate by [68Ga]Ga-PSMA-11 PET/CT was 100% (8/8) for lesion-based analysis, and 36.4% (4/11) for patient-based analysis, whereas those for [18F]FDG PET/CT were 12.5% (1/8) and 9.1% (1/11), respectively. [68Ga]Ga-PSMA-11 PET/CT led to a change in the clinical management of one (8.3%) patient. TBRBlood, and TBRLiver were significantly higher on [68Ga]Ga-PSMA-11 PET/CT than on [18F]FDG PET/CT (p = 0.018 and p = 0.038, respectively). Immunohistochemistry confirmed neovascular expression of PSMA in 55% of patients. Expression was significantly higher in patients with positive [68Ga]Ga-PSMA-11 PET/CT results (p = 0.042).Conclusions[68Ga]Ga-PSMA-11 PET/CT demonstrated higher detection rates than [18F]FDG PET/CT in both lesion-based and patient-based analyses.